(untitled) (Research, Society and Development, 2020)
Social isolation imposed on education the need for deep reflection. Demanding an emergency adaptation to remote connections and innovative teaching and learning methodologies. Schools, universities and institutes sought to reinvent possibilities and use technology, combined with creativity, so as not to run the risk of discontinuity throughout 2020. Both intellectual and operational efforts have been required from teachers and students. In this article, the results of a collective investigation on the aspects of the assignment of guidance by teachers who work in different courses and levels of education are presented. Contextualized the professional development of teachers and students, pointing to the opportunities and challenges inherent to the imposed social isolation. Thus, through this research, it was found that it is possible to consider the orientation activity as viable, but in a more challenging scenario, both for the maintenance of the students, avoiding their exclusion from this process, and for the self-motivation of their teachers.